Novel Covers As Literary Art - Khatib Nur Ali, Ahmad Jum’a (KnE Social Sciences, 2017)
Literary art is a translation, interpretation, transmutation of literary text from language system to another signs system. It is a perception product, interpretation and translation of its original works, not to be duplication but as a form of work of art. This research is intended to reveal Novel covers system of representation. The aim is to find out whether it represents the novel values or not as a literary art. In doing so, this research used qualitative method with Negeri van Oranje and Ayah covers as primary data. The data are chosen using purposive sampling with two basic standards: popularity and Myers design standards. Using representation theory and semiotic as tools of analysis, the research then finds that Negeri van Oranje and Ayah covers have two aspects of presentation: novel content values or theme and marketing aspect. It is presented using two elements: textual and visual. The marketing aspect mostly uses texts elements and the novel content uses visual elements. They are using symbolic signs to build future reader impression and perception of the novel. The symbolic signs and concept are constructed to represent the novel content messages or values. Text features explain the visual features, and the visual features express the text features. Covers have different representation system from the novel but it is not an independent system. In conclusion, not every novel cover can be literary art but Negeri van Oranje and Ayah novel covers can be included as literary art. Keywords: Literary arts, Novel Cover, Representation